Entesopathy of the lateral epicondyle of the humeral bone - current treatment options - Kamil Fatyga; Marta Tarczyńska; Krzysztof Gawęda; Rafał Mazur; Łukasz Głodek (Kazimierz Wielki University, 2020)
Chronic pain located on the lateral surface of the elbow in the area of the lateral epicondyle of the humerus is characteristic for a disease called tennis elbow, which belongs to the group of enthesopathies, i. e. diseases related to bone tendon attachment. The cause of the disease are micro-injuries caused by repetitive movements and chronic overloads. Degenerative changes occur in the tendons of the finger and wrist extensor muscles which attach to the lateral epicondyle of the humerus. The problem usually affects the extensor carpi radialis brevis muscle. A typical location for pain is the lateral side of the elbow joint but it can often radiate to the forearm and wrist. In our paper we presented the most commonly used and most effective methods of treatment of the disease. The least invasive methods of physiotherapy and rehabilitation include home exercise, ultrasound and phonophoresis, cryotherapy, light therapy, laser therapy and radial shock wave terapy. We compared the efficacy of pharmacological methods such as non-steroidal anti-inflammatory drugs, steroid injections with lidocaine, platelet-rich plasma, hyaluronic acid, botulinum toxin, collagen. We also mentioned the indications and surgical techniques of the tennis elbow.